Pengaruh Kreativitas dalam Peningkatan Kompetensi Kepemimpinan Alumni Magister Manajemen Pendidikan Pada Kurikulum Berbasis Kompetensi - Wardani, Krisma Widi (Kelola: Jurnal Manajemen Pendidikan, 2017)
This study aims to find out: 1) whether or not the leadership quality of the alumni of MMP FKIP UKSW is affected by creativity and curriculum; and 2) the determinants of the alumnis leadership level: creativity or curriculum factor. The participants of this research are those who have graduated (alumni) from MMP FKIP UKSW Salatiga, working in Temangung regency. There were as many as 35 alumni in 2014/2015 selected to join this research. The data was collected using self-rating scale consisting of 32 items that have been tested valid and reliable, then it was reduced to 3 variables. The analysis process was undertaken by using SPSS 24 assisted analysis technique. The result of this research showed that curriculum have nothing to do with the level of leadership. Meanwhile, alumniâs leadership level is significantly determined by the creativity. This finding is very important for the aspect of course quality improvement management that supposed to be conducted by professional lecturers. MMP FKIP UKSW refines its learning activities on creativity-based lectures which will bring positive influence on leadership level.